The implementation of metacognitive strategies in students’ teaching practice in microteaching class - Wahyuni, Hanna Irma; Kuswandono, Paulus (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
A B S T R A C T Microteaching classes can be a challenging area of negotiation between personal and professional values which can help and provide pre-service teachers understanding and opportunities to hone their teaching and learning process better. This research aims to identify the application of metacognitive strategies in the preparation process for teaching practice in microteaching classes, by focusing on the research questions regarding the implementation of metacognitive strategies in teaching practice exercises and students’s motivation to apply metacognitive strategies in micro-teaching classes. A qualitative case study method was used to answer these two research questions by employing purposive sampling with three participants in a micro-teaching class (semester five). The study reveals that students applied metacognitive strategies of goal-setting, planning, monitoring, and evaluating strategies to enhance their teaching practices. These strategies are influenced by internal and external motivation factors, such as intuition, personal experience, and self-awareness. Nevertheless, as this study involved a small group and did not focus on real classroom practices, future studies are suggested to involve more participants and combine methods to track both the immediate and long-term effects of using metacognitive strategies in teacher training.